2012
DOI: 10.1002/alr.21127
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated levels of human β‐defensins in patients with seasonal allergic rhinitis after allergen‐specific immunotherapy treatment

Abstract: The present study demonstrates an upregulation of HBD1 and HBD2 in SAR patients after completion of ASIT. This may reflect the importance of an intact innate immune response as part of our defense against infections among allergic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…HDM mice challenged with methacholine demonstrated methacholine dose-dependent increases in Penh levels, which were significantly reduced in SIT mice compared to HDM mice (Figure 2A , p<0.001). Having confirmed that induced IgG4 seems to suppress IgE levels, which was associated with treatment efficacy in allergic patients receiving subcutaneous immunotherapy [ 16 ]. SIT selectively removed long-lived IgE antibodies on mast cells [ 17 ].…”
Section: Resultsmentioning
confidence: 97%
“…HDM mice challenged with methacholine demonstrated methacholine dose-dependent increases in Penh levels, which were significantly reduced in SIT mice compared to HDM mice (Figure 2A , p<0.001). Having confirmed that induced IgG4 seems to suppress IgE levels, which was associated with treatment efficacy in allergic patients receiving subcutaneous immunotherapy [ 16 ]. SIT selectively removed long-lived IgE antibodies on mast cells [ 17 ].…”
Section: Resultsmentioning
confidence: 97%
“…In the study conducted by Bogefors et al (8), it was found that BD-1 and BD-3 expression in tonsillary tissues was lower in patients with AR compared with healthy controls. In another study, it was shown that BD-1 and BD-3 expressions significantly increased compared with the pre-treatment period in nasal biopsy samples of patients with AR after allergen-specific immunotherapy was completed (9). Similarly, Choi et al (18) found that BD-2 mRNA expression and protein levels in tonsillary and adenoid tissues of patients with AR were significantly lower compared with healthy controls.…”
Section: Discussionmentioning
confidence: 93%
“…Although the molecular mechanism of this has not been fully elucidated at the present time, it is thought that Th2 cytokines reduce defensin expression by leading to inhibition in the tumor necrosis factor (TNF)-α/ nuclear factor (NF)-κB system by way of signal transducer and activator of transcription (STAT) 6 activation (23,26). One of the reasons underlying the fact that immunotherapy increases BD-2 expression in the nasal mucosa may be the inhibition of Th2-type immune response by immunotherapy (9,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations of a group of AMPs, the human beta defensins (HBDs) have been performed in the upper respiratory tract. In these studies, a link between allergic status and expression of HBDs was revealed (Bogefors et al ., ). Similar connections were observed in other AMPs, such as S100A7 (also known as psoriasin; Bryborn et al ., ).…”
Section: Introductionmentioning
confidence: 97%